1997
DOI: 10.2134/jpa1997.0227
|View full text |Cite
|
Sign up to set email alerts
|

Ridge, Moldboard, Chisel, and No-Till Effects on Tile Water Quality beneath Two Cropping Systems

Abstract: Soil conservation tillage systems, including ridge-tillage, often reduce surface water contamination by pesticides because soil erosion and surface runoff are reduced. However, the effects on losses through subsurface drainage tile are somewhat uncertain. Our field study quantified the effects of four tillage practices in continuous corn (Zea mays L.) and corn-soybean [Glycine max (L.) Merr] rotations on herbicide and nitrate N losses in tile drainage water. Fertilizer and pesticide application methods were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 17 publications
10
117
0
2
Order By: Relevance
“…On average, RZWQM simulated a 14% reduction in drain flow under CC compared to CS. This is in agreement with other studies in the Midwest of the USA (Randall et al, 1997;Huggins et al, 2001), although Kanwar et al (1997) observed greater amounts of drain flow under CC than under CS rotation using 3 years of data (1990)(1991)(1992). As shown in Figs.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 92%
“…On average, RZWQM simulated a 14% reduction in drain flow under CC compared to CS. This is in agreement with other studies in the Midwest of the USA (Randall et al, 1997;Huggins et al, 2001), although Kanwar et al (1997) observed greater amounts of drain flow under CC than under CS rotation using 3 years of data (1990)(1991)(1992). As shown in Figs.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 92%
“…Long-term addition of plant residues under favorable conditions for decomposition and abundant rainfall could result in ideal conditions leading to leaching of organic P (7,31,32). Finally, preferential pathways for movement of water and nutrients are common under conservation tillage due to earthworm activity (10) and root channels (29). Potassium accumulated in the surface of both soils, regardless of tillage system, similar to results reported by Holanda et al (12) (Tables 3 and 4).…”
Section: Resultssupporting
confidence: 76%
“…3). Also, lime movement could have occurred via root channels and other pathways common under conservation tillage (29).…”
Section: Resultsmentioning
confidence: 99%
“…5 is 0.56, suggesting the rotation effect was only partially simulated and some effects such as increased infiltration due to additional surface residue (Weed and Kanwar, 1996) were not simulated. Greater drain flow from no-till continuous corn compared to notill corn-soybean rotations at Nashua was previously reported (Weed and Kanwar, 1996;Kanwar et al, 1997). These results suggest that the modified APSIM model is a promising tool to simulate daily tile drainage, average soil water fluctuation, and some management effects on yearly drainage.…”
Section: Drain Flowmentioning
confidence: 51%